Design, Construction and Research Application of a Differential Electrochemical Mass Spectrometer (DEMS) - Ashton, Sean James; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Sean Ashton's doctoral thesis, which he finished at the Technical University in Munich, describes the challenge of constructing a Differential Electrochemical Mass Spectrometer instrument (DEMS). DEMS combines an electrochemical cell with mass spectrometry via a membrane interface, allowing gaseous and volatile electrochemical reaction species to be monitored online. The thesis carefully introduces the fuel cell electrocatalyst development concerns before reviewing the pertinent literature on DEMS. This is followed by the presentation and discussion of the new extended design, including a thorough characterization of the instrument. The capabilities of the new setup are demonstrated in two research studies: The methanol oxidation reaction on Pt and PtRu catalysts, and the electrochemical corrosion of fuel cell catalyst supports. Despite both topics having long since been studied, new insights can be obtained through careful investigations with the new DEMS instrument that are of great, general interest. The thesis and the instrument thus show the way for future investigations in the field.
Differential Electrochemical Mass Spectrometry -- Design and Construction of the DEMS Instrument -- Practical Aspects of the DEMS Instrument -- Methanol Oxidation on HSAC Supported Pt and PtRu Catalysts -- The Electrochemical Oxidation of HSAC Catalyst Supports.
Keywords: Chemistry; Mass spectrometry; Catalysis; Chemistry; Electrochemistry; Mass Spectrometry; Catalysis